THE POETIC BRILLIANCE OF FEELINGS AND EXPERIENCES (Scientific journal of the Fergana State University, 2024)
This article examines G.Gulom's ability to use artistic images associated with the creative process. The pen, pencil case, paper, poem, poet and other images in the poet’s lyrics are analyzed. It is explained that these images allowed the poet to describe emotional experiences and reflect the boundless horizon of imagination and thinking. Ghulam gracefully polished through poetic images the feelings and experiences associated with the creative process, moments of inspiration. There is no doubt that studying them opens up the opportunity to look into the poet’s creative laboratory and observe creative moments in action. The opinions expressed in the article are briefly summarized by the researcher.